Code Mixing in Ali and Ratu Ratu Queens (2021): Sociolinguistics Study - Zakia Farah Oktofiani; Deden Novan Setiawan Nugraha (Linguistic, English Education and Art (LEEA) Journal, 2024)
The research aims to identify the types of code-mixing and the factors that affect the use of code-mixing in the movie Ali and Ratu Ratu Queens (2021) by analyzing the characters' dialogues. The research uses qualitative analysis to determine the types and factors of code mixing contained in the dialogues of the characters in the film. The findings of this study indicate types of code mixing according to Hoffman's theory–such as intra-lexical code-mixing, intra-sentential code-mixing, and involving a change of pronunciation–have appeared several times in the movie. In conclusion, the research underscores the complexity of code mixing in multilingual contexts portrayed in the movie, providing insights for further sociolinguistic studies. Keywords: Bilingualism, Code Mixing, Movie, Sociolinguistics